2005
DOI: 10.1002/pmic.200401186
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of putative plasmodesmatal proteins fromChara corallina

Abstract: Plasmodesmata are channels that bridge the cell walls of plant cells, allowing regulated transport of molecules between neighbouring cells. We have used a proteomic strategy to identify putative plasmodesmata-associated proteins in the giant-celled green alga Chara corallina. Proteins were extracted from the plasmodesmata-rich nodal complexes and the middle of the long internodal cells, which do not contain plasmodesmata. Comparison of protein spot patterns generated by two-dimensional gel electrophoresis of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 96 publications
1
38
0
1
Order By: Relevance
“…Several other works noted additional internal substructures (Ding et al 1992b, Overall and Blackman 1996. Recently, PD-associated proteins have been identified in charophycean algae and land plants , Blackman and Overall 1998, Gestel et al 2003, Faulkner et al 2005, Sagi et al 2005, Thomas et al 2008, Simpson et al 2009, Faulkner and Maule 2010. These works suggested that there are highly complicated control mechanisms underlying the cell-to-cell molecular traffic via PD.…”
Section: Introductionmentioning
confidence: 98%
“…Several other works noted additional internal substructures (Ding et al 1992b, Overall and Blackman 1996. Recently, PD-associated proteins have been identified in charophycean algae and land plants , Blackman and Overall 1998, Gestel et al 2003, Faulkner et al 2005, Sagi et al 2005, Thomas et al 2008, Simpson et al 2009, Faulkner and Maule 2010. These works suggested that there are highly complicated control mechanisms underlying the cell-to-cell molecular traffic via PD.…”
Section: Introductionmentioning
confidence: 98%
“…Information on how intercellular communication modulates development in charophyte algae is limited, but has been studied in some depth in male reproductive tissue (antheridia) in Chara, in which there is compelling evidence that remodeling of plasmodesmata is important for maintaining and coordinating cell division synchrony and developmental fate (Kwiatkowska 2003). In both embryophytes and charophyte algae, plasmodesmata can be formed during cytokinesis or secondarily in interphase cells by remodeling of walls and fusion of adjacent plasma membranes (Hepler 1982;Franceschi et al 1994), but the molecular details of plasmodesmata formation in charophyte algae and their degree of similarity to embryophyte plasmodesmata have not been established (Faulkner et al 2005;Timme and Delwiche 2010).…”
Section: Symplastic Connections and Intercellular Communicationmentioning
confidence: 99%
“…Furthermore, most cells in developing tissues undergo subsequent mitotic divisions giving rise to new populations of primary PD that are difficult to distinguish from secondary PD (Ehlers and Kollmann, 2001). The growing interest in novel PD proteins (Faulkner et al, 2005;Sagi et al, 2005;Levy et al, 2007;Thomas et al, 2008), and in the structure/function relations of PD (Oparka, 2004), prompted us to explore new methods for imaging PD.…”
Section: Introductionmentioning
confidence: 99%